2004
DOI: 10.1093/nar/gkh592
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of inositol phosphate-dependent mobility of Ku: depletion of the DNA-PK cofactor InsP6 inhibits Ku mobility

Abstract: Repair of DNA double-strand breaks (DSBs) in mammalian cells by nonhomologous end-joining (NHEJ) is initiated by the DNA-PK protein complex. Recent studies have shown inositol hexakisphosphate (InsP6) is a potent cofactor for DNA-PK activity in NHEJ. Specifically, InsP6 binds to the Ku component of DNA-PK, where it induces a conformational change and a corresponding increase in DNA end-joining activity. However, the effect of InsP6 on the dynamics of Ku, such as its mobility in the nucleus, is unknown. Importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…4). Similar data were obtained with chlorpromazine (Byrum et al, 2004), whereas KN-93 (500 M) and K-252a (50 M) calmodulin kinase inhibitors had no effect. Because it has been proposed that W-7 is cytotoxic (Jan et al, 2000), its effects were more systematically assessed.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…4). Similar data were obtained with chlorpromazine (Byrum et al, 2004), whereas KN-93 (500 M) and K-252a (50 M) calmodulin kinase inhibitors had no effect. Because it has been proposed that W-7 is cytotoxic (Jan et al, 2000), its effects were more systematically assessed.…”
Section: Resultssupporting
confidence: 79%
“…Nevertheless, an increasing number of inositol phosphates are being identified that have varied and diverse functions. In addition to calcium signaling, they have been implicated in nuclear mRNA export (York et al, 1999), chromatin remodelling (Shen et al, 2003;Steger et al, 2003), DNA repair (Hanakahi et al, 2000;Byrum et al, 2004), membrane trafficking (Ye et al, 1995;Saiardi et al, 2002), and control of cell proliferation (Orchiston et al, 2004).…”
mentioning
confidence: 99%
“…Recent studies have shown that inositol phosphates serve as cofactors for DNA-PK cs during NHEJ (28 -30). Notably, inositol hexakisphosphate (InsP 6 ) has been shown to regulate the mobility of Ku proteins and depletion of InsP 6 by the TFP-related compound chlorpromazine causes a reduction in the mobile fraction of Ku (31). Therefore, one might speculate that the inhibitory action of TFP on DNA DSB repair shown in this study could be a consequence of calmodulin antagonism.…”
Section: Discussionmentioning
confidence: 77%
“…Inositol hexakisphosphate (IP6) is a novel factor that is bound by DNA-PK and stimulates DNA end joining in vitro (41,42). Therefore, we used IP6 to stimulate DNA-PK activity in vitro in the presence/absence of Ku70/Ku86 subunits with FSYtide as substrate.…”
Section: Discussionmentioning
confidence: 99%